The Influence of “Pintu Berkah” FTV Program on The Saving Attitude - Ananda Salma Pebrianty; Ridwan Effendi; Kusnendi Kusnendi (Universitas Pendidikan Indonesia, 2021)
The aim of this research is to examine the profession of housewives who have an important role in a family, especially in managing finances for daily needs. The high level of spending in Indonesia causes people to have a wasteful lifestyle, but the adoption of a saving attitude can be influenced by other factors, for example television as a communication medium which can provide positive information content through television shows. This research uses quantitative methods by distributing questionnaires to collect data and applying moderated regression analysis. Questionnaires were distributed to 100 housewife respondents in Cisaranten Kidul Village with the criteria of watching the FTV program